RETRACTED: l-Arginine Uptake by Cationic Amino Acid Transporter Promotes Intra-Macrophage Survival of Leishmania donovani by Enhancing Arginase-Mediated Polyamine Synthesis - Mandal, Abhishek; Das, Sushmita; Kumar, Ajay; Roy, Saptarshi; Verma, Sudha; Ghosh, Ayan Kumar; Singh, Ruby; Abhishek, Kumar; Saini, Savita; Sardar, Abul Hasan; Purkait, Bidyut; Kumar, Ashish; et al. (Frontiers in Immunology, 2017)
The survival of intracellular protozoan parasite, Leishmania donovani, the causative agent of Indian visceral leishmaniasis (VL), depends on the activation status of macrophages. l-Arginine, a semi-essential amino acid plays a crucial regulatory role for activation of macrophages. However, the role of l-arginine transport in VL still remains elusive. In this study, we demonstrated that intra-macrophage survival of L. donovani depends on the availability of extracellular l-arginine. Infection of THP-1-derived macrophage/human monocyte-derived macrophage (hMDM) with Leishmania, resulted in upregulation of l-arginine transport. While investigating the involvement of the transporters, we observed that Leishmania survival was greatly impaired when the transporters were blocked either using inhibitor or siRNA-mediated downregulation. CAT-2 was found to be the main isoform associated with l-arginine transport in L. donovani-infected macrophages. l-arginine availability and its transport regulated the host arginase in Leishmania infection. Arginase and inducible nitric oxide synthase (iNOS) expression were reciprocally regulated when assayed using specific inhibitors and siRNA-mediated downregulation. Interestingly, induction of iNOS expression and nitric oxide production were observed in case of inhibition of arginase in infected macrophages. Furthermore, inhibition of l-arginine transport as well as arginase resulted in decreased polyamine production, limiting parasite survival inside macrophages. l-arginine availability and transport regulated Th1/Th2 cytokine levels in case of Leishmania infection. Upregulation of l-arginine transport, induction of host arginase, and enhanced polyamine production were correlated with increased level of IL-10 and decreased level of IL-12 and TNF-α in L. donovani-infected macrophages. Our findings provide clear evidence for targeting the metabolism of l-arginine and l-arginine-metabolizing enzymes as an important therapeutic and prophylactic strategy to treat VL.